The Response of Southeast Asian and Indonesian Islamists to the Futuh of the Taliban: A Reflection - Sahrasad, Herdi; Byhaqi, Imron; Chaidar, Al; Mulky, Mohamad Asrori; Dar, Mai (IAIN Ponorogo, 2021)
This article explains the purpose of establishing the Taliban, namely to restore peace, enforce sharia law, and maintain the Islamic character of Afghanistan. However, in responding to the futuh (the revolution, the victory) of the Taliban victory in Afghanistan on 15-17 August 2021, the Indonesian and Southeast Asian Islamists show differences. Â Indonesian Islamists and some radical Islamists in Southeast Asia, for instance, such as sympathizers supporting ISIS (Islamic State of Iraq and Syria) actually show the opposite attitude. IS or better known as ISIS (Islamic State of Iraq and Syria) considers the Taliban as a sworn enemy and branded them as infidels even though they have the same belief. Â The Taliban reject terrorism, even fighting ISIS terrorism and the like. In general, however, the Islamists in Indonesia show no euphoric response to the fall of Kabul instead of a plain hope that the Taliban government is able to rebuild a sovereign, inclusive, dignified, just and prosperous Afghanistan.